Some pedestrian banalities: the figure of the flaneur and contemporaneity - Barbieri, João Guilherme Sorpreso (2023)
This article deals with a way of looking at urban space, in addition to the ways of occupying the city and relating to time in contemporary times and part of the period understood as modern in art history. It also presents a small historical review about the flâneur, as well as establishing reflections on the experience and daily life. Finally, the concepts presented are analyzed and related to two Brazillian cinematographic Productions: Décimo Segundo Andar, 2016 and Viajo porque preciso, volto porque te amo, 2009. As a theoretical reference for the foundation of the article, there are theorists: Baudelaire (1988), Certeau (2012), Featherstone (2000) and Larrosa Bondía (2002).